TCAD for Si, SiGe and GaAs integrated circuits - Armstrong, G. A.; Maiti, C. K. (Institution of Engineering and Technology, 2007)
The 2005 International Technology Roadmap for Semiconductors (ITRS) predicts that the use of Technology computer-aided design (TCAD) will provide as much as a 40 per cent reduction in technology development costs by reducing the number of experimental lots and shortening development time for the semiconductor industry. In a highly competitive manufacturing environment, one needs to take the full advantage of the predictive power of TCAD to reduce cost and time for product development. Currently, process and device simulation has established itself as an indispensable tool for developing and optimising device and microelectronic process technologies in the R&D phase. With the device compact model parameter extraction for circuit analysis, TCAD can be extended into manufacturing for advanced process control and parametric yield analysis. Each chapter ensures coverage of up-to-date TCAD research results for state-of the-art devices and a comprehensive list of seminal references. In summary, this book fills a gap in the literature in a rapidly evolving field, as it blends together a wide ranging description of TCAD activities in Si, SiGe and GaAs materials, technology, device and their applications. An extensive reference list provided in each chapter will help the reader identify the key stages in the development of TCAD from early research through to its integration in current manufacturing.